Trait rumination in post-stress growth among Chinese college students: the chain mediating effect of distress disclosure and perceived social support - Wang, Zengjian; Xu, Yining; Zeng, Huifang (Frontiers in Public Health, 2023)
Background: Rumination has emerged as a significant factor contributing to personal growth following periods of stress or trauma. The present study aimed to investigate the relationship between trait rumination and post-stress growth (PSG) within the context of Chinese college students who encounter mild stressors in their daily lives. Moreover, we aim to evaluate the potential mediating roles played by both distress disclosure and perceived social support in this dynamic relationship.Method: All participants completed assessments using the Adolescent Self-Rating Life Events Checklist, Rumination Response Scale, Post-Stress Growth Inventory, Distress Disclosure Index, and Perceived Social Support Scale. Correlation and mediation analyses were conducted using SPSS PROCESS 4 MACRO.Results: All students reported experiencing mild psychological impacts as a result of negative life events in the past year and displayed moderate levels of PSG. There was no significant correlation observed between the effects of negative life events and PTG. Significant negative correlations were found between trait rumination and distress disclosure, perceived social support, and PSG. Distress disclosure and perceived social support jointly operated as sequential mediators in the relationship between trait rumination and PTG among all the participants. Qualitative analyses revealed different correlation patterns of high-versus low-ruminator.Trait rumination affects PSG both directly and indirectly, through its influence on distress disclosure and perceived social support. Our results emphasize the significance of actively participating in distress disclosure and nurturing a robust sense of social support to counteract the detrimental effects of rumination on post-traumatic growth among Chinese college students.